2019
DOI: 10.1002/nbm.4133
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptive denoising for chemical exchange saturation transfer MR imaging

Abstract: High image signal–to–noise ratio (SNR) is required to reliably detect the inherently small chemical exchange saturation transfer (CEST) effects in vivo. In this study, it was demonstrated that identifying spectral redundancies of CEST data by principal component analysis (PCA) in combination with an appropriate data–driven extraction of relevant information can be used for an effective and robust denoising of CEST spectra. The relationship between the number of relevant principal components and SNR was studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 56 publications
2
63
0
Order By: Relevance
“…An overview of the presented data processing pipeline is given in Figure . In vivo Z‐spectra are acquired at 3T and evaluated by conventional methods (PCA denoising, Lorentzian fitting). The obtained results are used to train a deep neural network to directly map from raw Z‐spectra to Lorentzian parameters, yielding CEST contrast maps in ~1 s where conventional evaluation takes ~10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the presented data processing pipeline is given in Figure . In vivo Z‐spectra are acquired at 3T and evaluated by conventional methods (PCA denoising, Lorentzian fitting). The obtained results are used to train a deep neural network to directly map from raw Z‐spectra to Lorentzian parameters, yielding CEST contrast maps in ~1 s where conventional evaluation takes ~10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Brain masks for each subject data set were created manually. The Z‐spectra were spectrally de‐noised by principal component analysis (PCA) following the approach of Breitling et al, keeping only the principal components suggested by the median criterion (Supporting Information Table ). To isolate CEST effects, a four‐pool Lorentzian fit model according to Goerke et al was used to fit the direct water saturation (DS), semi‐solid magnetization transfer (MT), amide proton transfer (APT), and relayed NOE peaks, using the model equationZΔω=c-LDS-LAPT-LNOE-LMT,with a constant c, the direct saturation poolLitalicDS=ADS1+)(Δω-normalδDSnormalΓDS/22,and the other poolsLi=Ai1+)(Δω-normalδDS-normalδinormalΓi/22,iAPT,NOE,MT,with amplitudes A i , full‐width‐at‐half‐maximum Γ i , and peak positions δ i .…”
Section: Methodsmentioning
confidence: 99%
“…The resulting Z ‐data were first denoised using an algorithm based on principal component analysis with the number of components determined according to the Malinowski criterion, and subsequently averaged to obtain the required nine Z ‐images. The final T protein contrast—as calculated from Equations and —was corrected for B 1 inhomogeneities by the “one‐point‐contrast correction” method .…”
Section: Methodsmentioning
confidence: 99%
“…To achieve this goal we applied several methodological developments: (i) implementation of cosine‐modulated pulses allowed for a simultaneous presaturation at two frequency offsets; and was additionally combined with (ii) a weighted acquisition scheme for optimal averaging. Furthermore, (iii) utilization of a 3D snapshot‐CEST image readout allowed for retrospective motion correction and (iv) facilitated the application of advanced denoising strategies . Preservation of specificity of the optimized dualCEST protocol was demonstrated in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…A joint authorship statement was mistakenly omitted from the article by Breitling et al The statement is given here:…”
mentioning
confidence: 99%